Synthesis and Antimicrobial Activity of Nitrogen-Containing Anthraquinone Derivatives - Shupeniuk, Vasyl; Tatiana Taras,; Oksana Sabadakh,; Eugene Luchkevich,; Mykola Matkivskyi , (Iraqi Journal of Pharmaceutical Sciences, 2022)
New substituted anthraquinones with amino derivations fragments were synthesized through the substitution of bromine atom by different amines using the Ullmann coupling reaction. Obtained compounds based on anthraquinone used for experimental antimicrobial studies. The structure of the synthesized compounds was confirmed by LC-MS and 1H, 13C NMR spectroscopy. Studies on planktonic microorganisms have shown that the first synthesized anthraquinone derivatives have an inhibitory effect against bacteria and fungi. The triazene 1-(3-(benzoic acid(triaz-1-en-1-ol(-4-(1H-imidazol-1-yl(-9,10-dioxo-9,10-dihydroanthracene -2-sulfonic acid, have wide spectrum of activity, growth retardation zones against gram-positive microorganisms in the range of 8.41-11.5 mm, gram-negative bacteria 5.87-8.18 mm, fungi of the genus Candida 5.81-7.48 mm. The high antimicrobial activity of this compound is probably due to the presence of benzoic acid in its molecule.